(untitled) (Journal of the College of Basic Education, 2022)
The oil industry in Iraq suffered from many difficulties, which led to the decline and weakness of oil production, the deterioration of the condition of refineries and pipelines for transporting crude oil, natural gas and oil derivatives, in addition to the weakness of the technological aspect, the spread of financial and administrative corruption, the high costs of rehabilitation, and administrative and organizational problems that are still continuing. And Iraq, as a country that possesses enormous oil wealth that allows it to play an important role in the international energy market, and has proven oil reserves that are the largest, has made the government budget dependent largely on oil revenues, and its strategic importance lies in financing most aspects of spending, as it is the first source of financial resources of foreign currencies. Thus, it faces a challenge in the deterioration of the administrative and technical conditions due to the wars (Iraqi-Iranian,